Legal problems of transfer pricing determination for digital assets in the Republic of Belarus - Khashkovsky, Nikita V. (Journal of the Belarusian State University. Law, 2026)
The problems of applying the transfer pricing mechanism to transactions involving digital assets are examined. The methodological inadequacy of the criterion based on the coincidence of codes from the National classifier of economic activities for determining comparable companies is substantiated, as well as the systemic limitations of the best match principle. It is proposed to supplement the legislation with substantive comparability criteria and to introduce a standalone special method for determining the transfer price in the absence of market comparables, applicable to digital and other hard-to-value assets.